2017
DOI: 10.1105/tpc.17.00543
|View full text |Cite
|
Sign up to set email alerts
|

MAPKs Influence Pollen Tube Growth by Controlling the Formation of Phosphatidylinositol 4,5-Bisphosphate in an Apical Plasma Membrane Domain

Abstract: An apical plasma membrane domain enriched in the regulatory phospholipid phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P] is critical for polar tip growth of pollen tubes. How the biosynthesis of PtdIns(4,5)P by phosphatidylinositol 4-phosphate 5-kinases (PI4P 5-kinases) is controlled by upstream signaling is currently unknown. The pollen-expressed PI4P 5-kinase PIP5K6 is required for clathrin-mediated endocytosis and polar tip growth in pollen tubes. Here, we identify PIP5K6 as a target of the pollen-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 65 publications
(135 reference statements)
1
49
0
Order By: Relevance
“…We could confirm this phosphorylation event in vitro using recombinant proteins (Appendix Fig S10A), and the modification of purified PI4Kb1 by purified MPK4 supports a direct physical interaction of the proteins in vitro (cf. In analogy to the in vitro inhibition of the phosphoinositide kinase PIP5K6 by the MAPK, MPK6 (Hempel et al, 2017), we then tested the catalytic activity of PI4Kb1 protein which had been prephosphorylated in vitro by MPK4, but found no change (Appendix Fig S10B). In analogy to the in vitro inhibition of the phosphoinositide kinase PIP5K6 by the MAPK, MPK6 (Hempel et al, 2017), we then tested the catalytic activity of PI4Kb1 protein which had been prephosphorylated in vitro by MPK4, but found no change (Appendix Fig S10B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could confirm this phosphorylation event in vitro using recombinant proteins (Appendix Fig S10A), and the modification of purified PI4Kb1 by purified MPK4 supports a direct physical interaction of the proteins in vitro (cf. In analogy to the in vitro inhibition of the phosphoinositide kinase PIP5K6 by the MAPK, MPK6 (Hempel et al, 2017), we then tested the catalytic activity of PI4Kb1 protein which had been prephosphorylated in vitro by MPK4, but found no change (Appendix Fig S10B). In analogy to the in vitro inhibition of the phosphoinositide kinase PIP5K6 by the MAPK, MPK6 (Hempel et al, 2017), we then tested the catalytic activity of PI4Kb1 protein which had been prephosphorylated in vitro by MPK4, but found no change (Appendix Fig S10B).…”
Section: Discussionmentioning
confidence: 99%
“…MPK4 acts in the Arabidopsis equivalent of the tobacco NACK-PQR pathway and is thus required for maintaining microtubule organization (Beck et al, , 2011. As we have previously described a regulatory link between MAPKs and phosphoinositide kinases in plants (Hempel et al, 2017), we next asked whether similarly MPK4 is functionally linked to the role of PI4Kbs in phragmoplast progression during cytokinesis. As we have previously described a regulatory link between MAPKs and phosphoinositide kinases in plants (Hempel et al, 2017), we next asked whether similarly MPK4 is functionally linked to the role of PI4Kbs in phragmoplast progression during cytokinesis.…”
Section: Of 26mentioning
confidence: 98%
“…The gel shift was more pronounced for myc‐MVQ1, in line with polyphosphorylation of this protein (Pecher et al ., ), whereas only two phosphorylation sites were reported for MPK6‐mediated phosphorylation of PIP5K6 (Hempel et al ., ). To characterize flg22‐dependent phosphorylation of PIP5K6 in more detail, we next analyzed PIP5K6‐HA in comparison to a PIP5K6‐HA AA variant, which can no longer be phosphorylated by MPK6, because residues T590 and T597 were substituted for alanines (Hempel et al ., ) (Fig. b).…”
Section: Resultsmentioning
confidence: 97%
“…So far, information on cytoplasmic effects of MAPKs is limited. We have previously reported that MPK6 influences pollen tube growth by targeting enzymes with key roles in the biosynthesis of phosphoinositides (PIs) at the plasma membrane (Hempel et al ., ). This finding suggests a regulatory link between MAPKs and PIs, which is probably not limited to pollen tubes and which we aimed to explore further.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation